John and Judaism : a contested relationship in context - Culpepper, R. Alan; Anderson, Paul N., 1956- (Atlanta SBL Press, 2017)
"The Gospel of John was written during the period of the emergence of Christianity and its separation from Judaism and bears witness to their contested relationship. This volume contains cutting-edge essays written by an international group of scholars who interpret for students and general readers what the book tells us about first-century Judaism, the separation of the church from Judaism, and how John's anti-Jewish references are being interpreted today"--
Includes bibliographical references (pages 355-412) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.